1970
DOI: 10.1128/jb.104.3.1338-1353.1970
|View full text |Cite
|
Sign up to set email alerts
|

Separation and Localization of Cell Wall Layers of a Gram-Negative Bacterium

Abstract: The cell envelope of a marine pseudomonad as seen in thin section by electron microscopy has the double-membrane structure typical of other gram-negative bacteria. Cells washed with a solution containing Na+, K+, and Mg++ at their concentrations in the growth medium, when suspended briefly in 0.5 M sucrose, lost 13% of their hexosamine in a form nonsedimentable by centrifugation at 73,000 x g. Since the resulting cells in thin section appeared unchanged, it was concluded that the material released was derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 33 publications
3
81
0
Order By: Relevance
“…This strain was originally isolated from a marine clam and has been classified as a Pseudomonas sp. type IV (Forsberg et al, 1970). It was grown at 25°C in a liquid medium containing 0.8% nutrient broth (bioMerieux 51101), 0.5% yeast extract (Difco 012701) in a salt solution consisting of 0.22 M NaC1, 0.026 M MgCl,, and 0.1 mM FeS04(NH,),S04~6H,0.…”
Section: Bacterial Strains and Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…This strain was originally isolated from a marine clam and has been classified as a Pseudomonas sp. type IV (Forsberg et al, 1970). It was grown at 25°C in a liquid medium containing 0.8% nutrient broth (bioMerieux 51101), 0.5% yeast extract (Difco 012701) in a salt solution consisting of 0.22 M NaC1, 0.026 M MgCl,, and 0.1 mM FeS04(NH,),S04~6H,0.…”
Section: Bacterial Strains and Mediamentioning
confidence: 99%
“…haloplanktis and P . fluorescens were prepared as described by Forsberg et al (1970). Stationary phase bacteria were harvested by centrifugation at 16,300 x g for 20 min at 4°C.…”
Section: Mureinoplast and Protoplast Preparationmentioning
confidence: 99%
“…Stained sections of marine pseudomonad B-16 (ATCC 19855) reveal that the cell envelope of this organism has a structure typical of other gram-negative bacteria (9). Since inorganic ions are required to maintain the cell envelope intact (2), control of the salt composition of the medium used to suspend the cells has led to a method for the separation of the various layers of the cell envelope of this organism (9). These studies have revealed that, in addition to the inner and outer membranous structures and the periplasmic space observed in stained thin sections, there is a layer which lies on the surface of the cell outside of the outer membrane structure.…”
Section: Thompson and Macleodmentioning
confidence: 99%
“…There is also a peptidoglycan layer closely apposed to the surface of the cytoplasmic membrane which is ordinarily not detectable in stained thin sections of cells of this organism (11), although such a layer is readily detectable in some other species of gram-negative bacteria (12). Thus, four cell wall layers lying outside of the cytoplasmic membrane of this organism have been detected (9). Since the methods used permit the separation of these layers from the cell and from each other, advantage has been taken of this fact to determine the location of alkaline phosphatase in the cell wall of this organism MATERIALS AND METHODS Organism, medium, growth, and harvesting of cells.…”
Section: Thompson and Macleodmentioning
confidence: 99%
See 1 more Smart Citation